A new species of Aphodius Illiger (Coleoptera: Scarabaeidae: Aphodiinae) from the central United States - Paulsen, M. J. (Zootaxa, 2006)
A new species of Aphodius Illiger, A. matiganae n.sp., is described from the central United States. The species is compared with A. rusicola Melsheimer and A. rubeolus Palisot de Beauvois, with which it has previously been confused.